Fisiopatologia da cefaléia crônica diária: estudo do líquido cefalorraquidiano - Vieira, Domingos Sávio de Souza [UNIFESP] (2008)
Introduction: Chronic daily headaches consist of a group of headaches, among them chronic migraine, that is comorbid with depression, overuse of medication, obesity and recently, cases of idiopathic intracranial hypertension without papilloedema. Objectives: To establish idiopathic intracranial hypertension without papilloedema prevalence and glutamate and gamma-aminobutyric acid levels in cerebrospinal fluid from patients with chronic migraine compared to other groups of patients. Methods: We studied patients with chronic migraine, who underwent lumbar puncture to rule out idiopathic intracranial hypertension without papilloedema. Amino acids glutamate and gamma-aminobutyric acid levels were measured by high performance liquid chromatography in cerebrospinal fluid. Results: Six patients, among sixty, had CSF open pressure higher than 200 mm H20 without papilloedema on fundoscopy. Patients who overused triptans had glutamate levels lower than those with abuse of other analgesic types and nonoverusers. The gamma-aminobutyric acid levels in cerebrospinal fluid were lower in depressed patients when compared to patients without depression and controls. Conclusions: The study of the cerebrospinal fluid was important in patients with chronic migraine for the exclusion of idiopathic intracranial hypertension without papilloedema, opening perspectives for the understanding of the physiopathology and development of new drug therapies for migraine and its comorbidities.